On differences in the equation-of-state for a selection of seven representative mammalian tissue analogue materials. (January 2018) - Appleby-Thomas, G.J.; Fitzmaurice, B.; Hameed, A.; Painter, J.; Gibson, M.; Wood, D.C.; Hazael, R.; Hazell, P.J.
Abstract: Tissue analogues employed for ballistic purposes are often monolithic in nature, e.g. ballistic gelatin and soap, etc. However, such constructs are not representative of real-world biological systems. Further, ethical considerations limit the ability to test with real-world tissues. This means that availability and understanding of accurate tissue simulants is of key importance. Here, the shock response of a wide range of ballistic simulants (ranging from dermal (protective/bulk) through to skeletal simulant materials) determined via plate-impact experiments are discussed, with a particular focus on the classification of the behaviour of differing simulants into groups that exhibit a similar response under high strain-rate loading. Resultant Hugoniot equation-of-state data (Us -up ; P-v) provides appropriate feedstock materials data for future hydrocode simulations of ballistic impact events. Highlights: Hugoniot equations-of-state derived for seven mammalian tissue analogues. Six dermal analogues and one skeletal simulant considered. Limitations of using monolithic ballistic tissue simulants identified. Potential route to reduce real-world tissue testing. Enhanced understanding of simulated complex constructs. Graphical abstract: